Neuritogenic activity of bi-functional bis-tryptoline triazole - Jutamas Jiaranaikulwanitch (2018)
© 2016 Elsevier Ltd Alzheimer's disease (AD) is a common neurodegenerative disorder, one of the hallmarks of which is the deposition of aggregated β-amyloid peptides (Aβ40,42) as plaques in the brain. Oligomers of these peptides have been reported to be toxic and to inhibit neurite outgrowth, as evidenced by neurite dystrophy and significant loss of synaptic connectivity of neurons in the AD brain resulting in cognitive decline. These peptides also react with biological metal in the brain to generate free radicals, thereby aggravating neuronal cell injury and death. Herein, multifunctional triazole-based compounds acting on multiple targets, namely β-secretase (BACE1), β-amyloid peptides (Aβ) as well as those possessing metal chelation and antioxidant properties, were developed and evaluated for neuritogenic activity in P19-derived neurons. At the non-cytotoxic concentration (1 nM), all multifunctional compounds significantly enhanced neurite outgrowth. New bis-tryptoline triazole (BTT) increased the neurite length and neurite number, by 93.25% and 136.09% over the control, respectively. This finding demonstrates the ability of multifunctional compounds targeting Aβ to enhance neurite outgrowth in addition to their neuroprotective action.